Serological diagnosis of strongyloidiasis: An evaluation of three commercial assays - Weitzel, Thomas; Dittrich, Sabine; Mockenhaupt, Frank P.; Lindner, Andreas K. (PLOS Neglected Tropical Diseases, 2024)
Author summary Strongyloidiasis is a neglected nematode infection, which causes significant morbidity and mortality due its chronic course and potential of severe manifestations. The disease mostly threatens inhabitants of tropical and subtropical regions. Moreover, it has been recognized as an emerging problem in industrialized countries affecting migrants and returning travelers. The diagnosis of the intestinal helminth is challenging, since its reliable detection in stool samples requires specific methods, which are mostly not performed. Antibody detection by serological tests is a practical and commercially available diagnostic alternative, but the capabilities of such tests in non-endemic regions are not sufficiently studied. The presented study evaluated the performance of three commercial Strongyloides ELISA kits using serum samples from travelers with proven strongyloidiasis or various other parasitic infections. The study revealed that the sensitivity of Strongyloides serology in patients from non-endemic countries, who often present with early infections, might be limited and that tests frequently cross-react with other helminth infections. Serological results should therefore be interpreted cautiously and used together with parasitological methods to reduce the risk of missing this potentially severe infection.